Humor-Based Coping Stress Images Explored in Side of Sense of Humor in Teachers Educators Children With Special Needs in Insan Mandiri Homeschooling Schools - Made Indah Pradnyasiwi; I Rai Hardika; Ni Nyoman Ari Indra Dewi (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
This study aims to find a picture of coping stress using humor that is explored in terms of the sense of humor in teachers of educators of children with special needs at Insan Mandiri Homeschooling schools. The research method used is qualitative method with case study approach. Data collection techniques use interviews, observations and documentation conducted on teachers teaching children with special needs. This study focuses on aspects of sense of humor consisting of humor production, coping with humor, humor appreciation and attitudes toward humor. The result of this study is that from teachers of educators of children with special needs who cope with stress with humor because the sense of humor that is owned is also supportive. Starting from being able to create humor well when experiencing stress, being able to manage humor as a way to reduce stress, appreciation of humor given also has a good impact on the success of coping strees and attitudes towards humor that are expressed by giving a feeling of pleasure to humor even though they experience stress pressure.